2010
DOI: 10.1063/1.3447773
|View full text |Cite
|
Sign up to set email alerts
|

Minimal unitary representation of SU(2,2) and its deformations as massless conformal fields and their supersymmetric extensions

Abstract: We study the minimal unitary representation (minrep) of SO(4, 2) over an Hilbert space of functions of three variables, obtained by quantizing its quasiconformal action on a five dimensional space. The minrep of SO(4, 2), which coincides with the minrep of SU (2, 2) similarly constructed, corresponds to a massless conformal scalar in four spacetime dimensions. There exists a one-parameter family of deformations of the minrep of SU (2, 2). For positive (negative) integer values of the deformation parameter ζ, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(120 citation statements)
references
References 51 publications
(156 reference statements)
2
118
0
Order By: Relevance
“…In previous work we gave a construction of the minimal unitary realization of the Lie algebra of four-dimensional conformal group SU (2,2) and showed that it admits a one-parameter family of deformations [1]. The minimal unitary representation (minrep) and its deformations describe all the massless conformal fields in four dimensions, and the deformation parameter is simply the helicity which can take on continuous values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work we gave a construction of the minimal unitary realization of the Lie algebra of four-dimensional conformal group SU (2,2) and showed that it admits a one-parameter family of deformations [1]. The minimal unitary representation (minrep) and its deformations describe all the massless conformal fields in four dimensions, and the deformation parameter is simply the helicity which can take on continuous values.…”
Section: Introductionmentioning
confidence: 99%
“…These results were also extended to the superalgebras SU (2, 2|N), and it was shown that minimal unitary supermultiplet and its deformations describe massless N -extended superconformal multiplets in four dimensions. For PSU (2, 2|4), the minimal unitary supermultiplet is simply the N = 4 Yang-Mills supermultiplet [1].…”
Section: Introductionmentioning
confidence: 99%
“…Notice also that for the sl N series, the quantization or equivalently the minimal representation is not unique but is of one-parameter family labeled by λ. For the sl 4 case, the minimal representation has been studied also in [52].…”
Section: Jhep05(2014)103mentioning
confidence: 99%
“…Much progress has been made on the subject of minimal representations, see for example [40][41][42][43][44][45][46][47][48][49][50] and references therein. In physics literature, the minimal representations of isometry algebras are explored to a large extent by Gunaydin and collaborators [51][52][53][54][55].…”
Section: Jhep05(2014)103mentioning
confidence: 99%
“…We choose a particular type of (massless discrete series) positive-energy unitary irreps 10 H n known as "minireps" or doubletons [34][35][36], which have the remarkable property that they remain irreducible 11 under SO(4, 1) ⊂ SO(4, 2). They have positive discrete spectrum…”
Section: Jhep02(2018)033mentioning
confidence: 99%